PERAN BADAN PERWAKILAN DESA DALAM MEMBANGUN PARTISIPASI MASYARAKAT TERHADAP PERKEMBANGAN DESA - Faradila Arrahma; Reza Pahlevi; Muhammad Yusuf Faraby; Bambang Setiawan; Moch. Gufron Latif (JOURNAL SAINS STUDENT RESEARCH, 2024)
The purpose of this study is to analyze the role of the Village Representative Council in building community participation towards village development. Community participation is an essential element of sustainable development, and as the BPD is a representative institution at the village level, it has a strategic responsibility to facilitate citizen participation. The research methodology used in this study is a qualitative approach with data collection methods used, namely in-depth interviews and participatory observation in several villages. The result of the research is that the BPD functions as a bridge between the village government and the community, educates the community on the importance of participation, and organizes networking forums that allow the aspirations of the community to be included. In addition, the BPD also plays a role in designing development programs that are responsive to the needs of the community. However, the challenge is low community awareness and the lack of capacity of the Village Representative Council to facilitate participation. The conclusion of this study is that by improving the role of the Village Representative Council and the capacity of its members, community participation will become more active in village development.